Discovery of a para-Acetoxy-benzyl Ester Prodrug of a Hydroxamate-Based Glutamate Carboxypeptidase II Inhibitor as Oral Therapy for Neuropathic Pain - Rais, Rana; Vávra, Jan; Tichý, Tomáš; Dash, Ranjeet P; Gadiano, Alexandra J; Tenora, Lukáš; Monincová, Lenka; Bařinka, Cyril; Alt, Jesse; Zimmermann, Sarah C; Slusher, C Ethan; Wu, Ying; et al. (Journal of medicinal chemistry, 2017)
4-Carboxy-α-[3-(hydroxyamino)-3-oxopropyl]-benzenepropanoic acid 1 is a potent hydroxamate-based inhibitor of glutamate carboxypeptidase II. In an attempt to improve its poor oral pharmacokinetics, we synthesized a series of prodrugs by masking its hydrophilic hydroxamate group. Prodrugs were evaluated for oral availability in mice and showed varying degree of plasma exposure to 1. Of these, para-acetoxybenzyl-based, 4-(5-(((4-acetoxybenzyl)oxy)amino)-2-carboxy-5-oxopentyl)benzoic acid, 12, provided 5-fold higher plasma levels of 1 compared to oral administration of 1 itself. Subsequently, para-acetoxybenzyl-based prodrugs with additional ester promoiety(ies) on carboxylate(s) were examined for their ability to deliver 1 to plasma. Isopropyloxycarbonyloxymethyl (POC) ester 30 was the only prodrug that achieved substantial plasma levels of 1. In vitro metabolite identification studies confirmed stability of the ethyl ester of benzoate while the POC group was rapidly hydrolyzed. At oral daily dose-equivalent of 3 mg/kg, 12 exhibited analgesic efficacy comparable to dose of 10 mg/kg of 1 in the rat chronic constrictive injury model of neuropathic pain.
Keywords: kyseliny hydroxamové; neuralgie; Male; Analgesics; Glutamate Carboxypeptidase II; esterifikace; Animals; prekurzory léčiv; Humans; Mice; Hydroxamic Acids; aplikace orální; Enzyme Inhibitors; mužské pohlaví; inhibitory enzymů; Neuralgia; krysa rodu Rattus; glutamátkarboxypeptidasa II; Rats; Rats, Sprague-Dawley; objevování léků; Administration, Oral; analgetika; Drug Discovery; zvířata; Prodrugs; potkani Sprague-Dawley; lidé; Esterification; myši